2014
DOI: 10.5194/tcd-8-2277-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of changing sea ice on the vulnerability of Arctic coasts

Abstract: Abstract. Shorefast sea ice prevents the interaction of the land and the ocean in the Arctic winter and influences this interaction in the summer by governing the fetch. In many parts of the Arctic the sea-ice-free season is increasing in duration, and the summertime sea ice extents are decreasing. Sea ice provides a first order control on the vulnerability of Arctic coasts to erosion, inundation, and damage to settlements and infrastructure. We ask how the changing sea ice cover has influenced coastal erosion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This corroborates with findings in the literature that link accelerated erosion to high storm surges (Kobayashi et al, 1999;Leont'yev, 2003;Barnhart, Overeem, et al, 2014). The more sensitive variables (i.e.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This corroborates with findings in the literature that link accelerated erosion to high storm surges (Kobayashi et al, 1999;Leont'yev, 2003;Barnhart, Overeem, et al, 2014). The more sensitive variables (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Variations in sediment and ice composition along the coastline will subsequently lead to variations in erosion rates. In general, ice content exerts a strong positive influence on erosion rates (Barnhart, Overeem, et al, 2014;Kobayashi et al, 1999) …”
Section: Ice and Sediment Compositionmentioning
confidence: 99%
“…In addition, landfast ice breakup and ice-free conditions in the Beaufort Sea occurred 19 and 39 days earlier, respectively, in the period 2000-2007than in 1973-1977(Mahoney et al 2014. Duration of wave setup and increased wave height show significant positive trends as the length of the open water season in the Beaufort Sea increased by factor 1.9 from 1979 to 2012 (Barnhart et al 2014b). The lengthening open water season resulted in anomalously high surface water temperatures in the most of the Arctic Ocean including the Beaufort Sea (Steele et al 2008), which is another factor that drives erosion of icerich permafrost coasts (Aré 1988;Barnhart et al 2014a;Kobayashi et al 1999;Ravens et al 2012) and may help explain the accelerating trend observed by the current study.…”
Section: Discussion Shoreline Dynamicsmentioning
confidence: 93%
“…The lengthening open water season resulted in anomalously high surface water temperatures in the most of the Arctic Ocean including the Beaufort Sea (Steele et al 2008), which is another factor that drives erosion of icerich permafrost coasts (Aré 1988;Barnhart et al 2014a;Kobayashi et al 1999;Ravens et al 2012) and may help explain the accelerating trend observed by the current study. These changes result in increasing vulnerability of Arctic coasts to erosion (Barnhart et al 2014b). …”
Section: Discussion Shoreline Dynamicsmentioning
confidence: 99%
“…The high rates of erosion observed along the coasts of northern Eurasia and North America have been linked with thermoabrasion of ground ice directly exposed to the operation of coastal processes (Are 1988;Wobus et al 2011). The acceleration in the rate of abrasion has been associated with both the extension of the ice−free period and an increase in the number of storms entering Arctic region (Lambert 2004;Barnhart et al 2014). In their seminal paper on Arctic coastal erosion, Lantuit et al (2012) analysed 61,000 km of Arctic coast and reported a mean erosion rate of 0.5 m a −1 .…”
Section: Introductionmentioning
confidence: 99%